One Bloodline, Multiple Religiosities: Malay-speaking Hadramis on Being ‘Moderate-most’ Muslims in Contemporary Indonesia - Taufik, Egi Tanadi; Kurniawan, Syamsul; Suprianto, Bibi; Fitriyani, Feny Nida; Miftah, Muhammad (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2024)
Internal contestation within Muslim communities over who embodies the ideal of moderation is often problematic, including among the descendants of the 18th-century Hadrami Arab diaspora in the Archipelago. Through qualitative research focusing on the Hadrami community dynamics in Pontianak, this article reveals divisions and internal conflicts within the community, leading to a contest over who could claim to be the most moderate. The study situates the exceptionalism of Hadrami elites in Pontianak within a